Knowledge and practice on prevention of mosquito-borne diseases in livestock-keeping and non-livestock-keeping communities in Hanoi city, Vietnam: A mixed-method study - Thang Nguyen-Tien; Long Thanh Pham; Duoc Trong Vu; Son Hai Tran; Lieu Thi Vu; Vuong Nghia Bui; Anh Ngoc Bui; Trung Duc Hoang; Thanh Thi Vu; Hung Nguyen-Viet; Magnusson, Ulf; Lundkvist, Å.; et al. (Public Library of Science, 2021)
Mosquito-borne diseases (MBDs) are causing high morbidity and mortality for humans. Urban livestock keeping is still common in cities around the world. The animals may serve as reservoirs for zoonotic MBDs, which increase the risks for humans. Here we assess the knowledge and practices related to MBDs in households with livestock and without livestock and explore the perceptions of the health care sector about MBDs and livestock keeping in Hanoi city of Vietnam in a cross-sectional study. A quantitative survey was conducted including 513 households with and without livestock-keeping in six districts and complemented with qualitative surveys with four health staff from Hanoi Center of Disease Control and three district health centers. The quantitative survey indicated that the participants possessed basic knowledge on MBDs with an average score of 18.3 out of 35, of which non-livestock-keeping households had a better knowledge than households keeping livestock (p<0.05). Both household categories had low score, 3.5 out of 11, regarding preventive practices against MBDs. The negative binomial model showed that occupation and location of living were factors associated to the knowledge on MBDs. Farmers were likely to have better preventive practices as compared to office workers (p<0.05). Those who had better knowledge also had more adequate preventive practices against MBDs (p<0.001). The qualitative survey revealed that livestock keeping was determined as increasing risks of MBDs due to the increase of mosquito population. It is recommended that community campaigns to raise the awareness and change behavior on MBDs should be organized based on collaboration between the health sector and the veterinary sector for households with and without livestock living in central urban and peri-urban areas. Further studies are needed to confirm the association between urban livestock keeping and potential increasing risks of MBDs such as dengue and Japanese encephalitis.